COLLABORATIVE DIGITAL TRANSFORMATION PEMERINTAH DAERAH DI INDONESIA - Rio Yusri Maulana (Universitas Muhammadiyah Sorong, 2022)
This article is intended to contribute as an additional new reference for academics and practitioners in the field of government science and to introduce the concept of developing digital government transformation that focuses on collaboration in Indonesian local governments. This article uses case studies and a limited literature review to explore how collaboration can play an important role in the implementation of digital transformation in the West Java Digital Service (JDS), or the Regional Technical Implementation Unit of the Center for Digital Services, Geospatial Data and Information under the West Java Provincial Communication and Information Office. As a digital-based local government agency, Indonesia has the goal of being an accelerator of achieving government targets to break the digital divide for remote communities, improve the efficiency and accuracy of data and technology-based community data policies, support services and community policy making that are responsive, adaptive, and innovative. This article provides an overview of how Indonesian local governments deliver digital-based policies through joint decision-making or collaborative governance, seeking to share decision-making power with stakeholders to develop joint recommendations for effective and lasting solutions to public problems.